(3QSGdI aj PcQ GdbGQhQI hCMhGdgG hPcQ GdESJOGd HgG Ydi GdeRGL GdGfSGfis - (3CHhHcQ GdQGRj , eMeO Hf RcQjG, CHh HcQ GdQGRj,J (B311 (3g` s ((3CMeO Hf TaGei GdWjH s)
(3ChdgG (B:s
(3GdMeO ddg hGgH GdYbd MeOG jeJQi GdeRjO hbO hLO dc CSYOc Gddg eJYLHkG ef JQc LGdjfhS GaQGO cJGH SJbU aj CMhGd GdHhd s
(3BNQgG (B:s
(3hMQcGJ YQhb ScGf GdHdGO GdMGQI cGdRfhL hGdfhHI eJZjQI dGfHKGJ GdbhI hbdJgG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI WgQGf (B(1435) s
Keywords: (3GdWHs